How eco-clubs foster pro-environmental behavior in a school context: a case from Finland - Anssi Huoponen (Fennia: International Journal of Geography)
Promoting pro-environmental behavior with environmental education (EE) has been proven to be challenging due to various school and student-related barriers. Eco-clubs are a widely used pathway in EE, which may help to overcome these barriers. Despite the popularity of eco-clubs, few studies have been conducted on the topic. This study approaches this problem with a case study to examine students’ perceptions of an eco-club in a Finnish general upper secondary school. In the study, 14 of the schools’ eco-club students participated in group interviews, which focused on their perceptions of the eco-club and its activities. Additionally, 100 non-eco-club students participated in a qualitative survey about their perceptions of the eco-club. This study found that eco-club students consider the club important in supporting their environmental actions in the school. They also find the club’s atmosphere and community to be a crucial part of supporting these actions. The members also find that the participation of peers and practical things enable the eco-club activities, while external influences, lack of time, and the reluctance of peers act as a barrier. The results indicate that there is a contradiction between the members’ and non-members’ perceptions of the eco-clubs’ effect on students and the school. While members find the eco-club important in supporting the environmental actions of the students and the school and spreading their influence outside of the school, the lack of knowledge dominates non-members’ perceptions, and some of them find the eco-club unimportant. Based on this research, eco-clubs seem to be a promising pathway in promoting members’ pro-environmental behavior while the club’s influence outside of the club remains small.